Aspects of Consumer Protection for Online Shop Business Actors in Delivery Service Negligence - Raissa Kemala Dewi; Alip Rahman; Siska Karina (Pelopor Publikasi Akademika, 2026)
The rapid growth of e-commerce puts delivery service companies as a crucial element in the distribution chain. However, this dynamic often raises a gap in losses for online shop business actors due to expedition negligence and inequality in the bargaining position in the use of standard clauses. Because of this polemic, this study questions how the legal protection mechanism is able to protect online shop business actors when facing the negligence of the shipper. Therefore, the research was directed to identify proportionate forms of legal protection as well as analyze the effectiveness of the compensation claim process based on Law Number 8 of 1999 concerning Consumer Protection. In order to unravel these problems, a normative juridical approach enriched with qualitative data is used through tracing of rules, interviews, and observations at J&T Kargo Kesambi. The results of the study revealed that there is an empirical clash between the principle of absolute responsibility in regulation and the practice of including exoneration clauses that unilaterally limit the value of compensation. Insurance facilities often shift into an instrument of release of the responsibility of service providers, forcing business actors to bear absolute financial risks if they do not use them. The fulfillment of this right is further hampered by claim procedures, such as the absolute obligation to include unboxing videos.